Optogenetic stimulation of CA3 pyramidal neurons restores synaptic deficits to improve spatial short-term memory in APP/PS1 mice. (February 2022) - Yang, Qinghu; Song, Da; Xie, Zhen; He, Guiqiong; Zhao, Juan; Wang, Zhe; Dong, Zhifang; Zhang, Heao; Yang, Liang; Jiang, Ming; Wu, Yili; Shi, Qing; et al.
Highlights: Optogenetic stimulation of hippocampal CA3 PNs restores the spatial memory in APP/PS1 mice. Stimulation of CA3 PNs enhanced the synaptic plasticity and activated astrocytes. Inhibition of CA3 astrocytes reversed the effects of CA3 PNs stimulation. Abstract: The hippocampal CA3 region, that is involved in the encoding and retrieval of spatial memory, is found to be synaptically impaired in the early-onset of Alzheimer's disease (AD). It is reported optogenetic manipulation of DG or CA1 can rescue the memory impairment of APP/PS1 mice, however, how CA3 region contributes to AD-related deficits in cognitive function is still unknown. Our work shows optogenetic stimulation of CA3 pyramidal neurons (PNs) significantly restores the impaired spatial short-term memory of APP/PS1 mice. This enhances the anatomical synaptic density/strength and synaptic plasticity as well as activates astrocytes. Chemogenetic inhibiting the activity of CA3 astrocytes reverses the effect of optogenetic stimulation of CA3 PNs that leads to reduced anatomical synaptic density/strength, decreased synaptic protein and AMPA receptors GluA3/4, thus disrupting the cognitive restoration of APP/PS1 mice. These results reveal the molecular mechanism of optogenetic activation of CA3 PNs on restoration of the spatial short-term memory of APP/PS1 mice and unveil a potential strategy of manipulating CA3 for AD treatment.